miRNA profiling of cancer - Di Leva, Gianpiero (2013)
A steadily growing number of studies have shown that microRNAs have key roles in the regulation of cellular processes and that their dysregulation is essential to keep the malignant phenotype of cancer cells. The distorted and unique expression profile of microRNAs in different types and subsets of tumor coupled with their presence in biological fluids make of microRNAs an attractive source of sensitive biomarkers. Here, we will discuss how microRNA profiles are altered in cancer, highlighting their potential as sensitive biomarkers for cancer risk stratification, outcome prediction and classification of histological subtypes. We will also evaluate the current knowledge on the use of microRNAs as circulating biomarkers, hoping that further studies will lead to the application of microRNA signature in prognostic and predictive markers that can improve patient health.